A preparation method of nano-alumina dispersion with high solid content and its product

Nanoalumina powder was synthesized by high-temperature gas-phase hydrolysis method and dissolved in deionized water. Relevant parameters were controlled, and the problems of poor fluidity and easy coagulation of high-solid content nanoalumina dispersion were solved, thereby achieving efficient and stable preparation of nanoalumina dispersions, improving the quality of ceramics and polishing liquids.

CN119774643APending Publication Date: 2025-04-08NANTONG JIANGSHAN NEW ENERGY TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411790514.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

It is difficult to prepare a nano-alumina water-based dispersion with high solid content and excellent fluidity in the prior art, resulting in the nano-alumina powder being easily condensed under high solid content, affecting the quality of ceramic materials and polishing liquid.

Method used

The nano-alumina powder was synthesized by high-temperature gas-phase hydrolysis method, and dissolved it in deionized water. The reaction temperature and particle size, moisture content, pH value, zeta potential and other parameters of the powder were controlled to obtain a stable high-solid content nano-alumina dispersion liquid.

Benefits of technology

The nano-alumina dispersion prepared by this method has excellent fluidity and storage stability, avoids condensation, and improves the application performance of nano-alumina in ceramics and polishing liquids.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175202010000081
    Figure BDA0005175202010000081
  • Figure BDA0005175202010000091
    Figure BDA0005175202010000091
  • Figure HDA0005175202020000011
    Figure HDA0005175202020000011
Patent Text Reader

Abstract

The present invention relates to the technical field of nano material preparation, and specifically to a preparation method of a high solid content nano alumina dispersion and its product, which at least includes the following steps: S1, synthesizing nano alumina powder by high temperature gas phase hydrolysis method; S2, dissolving the prepared nano alumina powder in deionized water; the high temperature gas phase hydrolysis method is to react gasified elemental aluminum with chlorine to form gaseous aluminum trichloride, and then react with water vapor to form nano alumina powder. By controlling the reaction temperature and simultaneously limiting the median particle size, water content, pH value, zeta potential, angle of repose and other parameters of the prepared nano alumina powder, the problems of viscosity, poor fluidity and easy coagulation of nano powder at high solid content are solved, and the defects of easy scratching and pores of nano alumina in the use process of polishing liquid, ceramics and other fields are improved, which is of great significance to the quality improvement of nano powder and its industrial production application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano material preparation, and in particular to a preparation method of a high-solid content nano alumina dispersion and a product thereof. Background Art

[0002] The colloidal molding process required for the preparation of high-performance special ceramic materials and the chemical mechanical polishing technology used for surface precision machining are highly dependent on the water-based dispersion of nano-alumina with high solid content and stable dispersion. The suspension stability of the dispersion is directly related to the quality of the final product. In the water-based dispersion system of nano-alumina with a high solid content, Brownian motion will significantly enhance the collision frequency between nanoparticles, prompting the natural formation of agglomerates, which will then easily evolve into micro-agglomerate structures. These tiny agglomerates continue to collide with each other, gradually increase in size, and eventually lead to precipitation or coagulation. These precipitations and coagulations will not only cause defects such as unevenness and pores in the ceramic colloidal molding products, but will also damage the surface of the workpiece during the chemical mechanical polishing process, which seriously restricts the development of nano-alumina special ceramic materials and polishing fluids.

[0003] Due to their extremely high surface energy, nanoparticles are subject to complex forces in water, including van der Waals forces, double-layer repulsion, solvation effect, hydrogen bond bridging force, etc. At the same time, at the same content, nanoparticles have smaller spacing than micron particles and are more likely to agglomerate. Therefore, it is crucial to ensure the stability and rheological properties of nanoparticles in water. At present, the key issue that needs to be solved in this field is how to prepare a water-based dispersion of nano-alumina with excellent fluidity and stability to improve the dispersion stability of particles and product quality.

[0004] Chinese patent CN102502745A discloses a method and device for manufacturing nano-alumina powder, which uses elemental aluminum, chlorine and water as main raw materials and synthesizes nano-alumina powder by chemical vapor method; Chinese patent CN1810646A discloses a continuous preparation process for high-purity nano-alumina, in which aluminum trichloride is continuously passed through a premixer after high-temperature gasification, and then enters a reaction chamber after being fully mixed with hydrogen and oxygen. Aluminum trichloride uses the high temperature and water generated by the combustion of hydrogen and oxygen in the reaction chamber to undergo high-temperature hydrolysis and condensation reaction, and the reaction product is subjected to aggregation, gas-solid separation, dechlorination, flotation and other processes to obtain high-purity nano-alumina. However, the nano-alumina powder prepared by the above process still has the problems of viscous solution, poor fluidity and easy agglomeration under high solid content. Summary of the invention

[0005] In order to solve the problems in the prior art, the first aspect of the present invention provides a method for preparing a high solid content nano-alumina dispersion, which comprises at least the following steps:

[0006] S1. Synthesizing nano-alumina powder by high temperature gas phase hydrolysis method;

[0007] S2. Dissolve the prepared nano-alumina powder in deionized water to obtain.

[0008] The high-temperature gas phase hydrolysis method is to react gasified elemental aluminum with chlorine to form gaseous aluminum trichloride, and the gaseous aluminum trichloride reacts with water vapor to form nano-alumina powder.

[0009] In one embodiment, the flow rate of the gaseous aluminum chloride is 0.02 mol / s.

[0010] In one embodiment, the temperature of the reaction of gaseous aluminum chloride and water vapor is 500-800°C.

[0011] In a preferred embodiment, the reaction temperature of the gaseous aluminum chloride and water vapor is selected from any one of 500°C, 600°C, 700°C, and 800°C.

[0012] In one embodiment, the water vapor flow rate is 0.2 mol / s.

[0013] In one embodiment, the median particle size D50 of the nano-alumina powder is less than 1 μm.

[0014] In a preferred embodiment, the median particle size D50 of the nano-alumina powder is selected from any one of 0.104 μm, 0.108 μm, and 0.118 μm.

[0015] In one embodiment, the water content of the nano-alumina powder is less than 5%.

[0016] In a preferred embodiment, the moisture content of the nano-alumina powder is selected from any one of 3.34%, 3.55%, 3.89% and 4.17%.

[0017] In one embodiment, the pH value of the nano-alumina powder is 3.5-4.5.

[0018] In a preferred embodiment, the pH of the nano-alumina powder is selected from any one of 3.5, 4.01, 4.07, 4.14, 4.24, and 4.5.

[0019] In one embodiment, the zeta potential of the nano-alumina powder is 6-10 mV.

[0020] In a preferred embodiment, the zeta potential of the nano-alumina powder is selected from any one of 6 mV, 6.1 mV, 7.3 mV, 7.7 mV, 8.5 mV, and 10 mV.

[0021] In one embodiment, the angle of repose of the nano-alumina powder is 35-45°.

[0022] In a preferred embodiment, the repose angle of the nano-alumina powder is selected from any one of 35°, 36°, 39°, 41°, 42°, and 45°.

[0023] In one embodiment, the bulk density of the nano-alumina powder is 0.03-0.06 g / mL.

[0024] In a preferred embodiment, the bulk density of the nano-alumina powder is selected from any one of 0.03 g / mL, 0.0307 g / mL, 0.0369 g / mL, 0.04 g / mL, 0.0479 g / mL, 0.05 g / mL, 0.0549 g / mL, and 0.06 g / mL.

[0025] The second aspect of the present invention provides a solid content nano-alumina dispersion product prepared by the above preparation method.

[0026] In one embodiment, the solid content of the nano-alumina powder in the product is 10-30wt%, which can be 10wt%, 20wt%, or 30wt%.

[0027] The high solid content of the nano-alumina dispersion with high solid content in the present invention is specifically explained as the solid content of the nano-alumina powder in the dispersion being 10-30wt%.

[0028] Beneficial Effects

[0029] 1. The present invention controls the reaction temperature and simultaneously limits the median particle size, moisture content, pH value, zeta potential, angle of repose and other parameters of the prepared nano-alumina powder, thereby solving the problems of viscous solution, poor fluidity and easy agglomeration of nano-powders at high solid content.

[0030] 2. The preparation method provided by the present invention does not require complicated post-processing, and can obtain a nano-alumina dispersion with excellent fluidity and stable storage without adding stabilizers or dispersants.

[0031] 3. The nano-alumina solution prepared by the present invention still has excellent fluidity even at a high solid content, thereby improving the defects of nano-alumina such as easy scratching and pores during use in the fields of polishing liquid, ceramics, etc.

[0032] 4. The present invention overcomes the problems of viscosity, poor fluidity, and easy coagulation of nano-alumina dispersions used for polishing liquids, ceramic slurries, and additives at high solid content, and provides an effective way to prepare nano-alumina dispersions with high solid content.

[0033] 5. The preparation method provided by the present invention is simple to operate, rapid and effective, and improves the dispersibility and fluidity of high-solid content nano-alumina, which is of great significance for improving the quality of nano-powders and their industrial production applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 , the fluidity picture of the high solid content nano-alumina dispersion of Example 1 after being stored for two months;

[0035] Figure 2 , the fluidity picture of the high solid content nano-alumina dispersion of Example 2 after being stored for two months;

[0036] Figure 3 , the fluidity picture of the high solid content nano-alumina dispersion of Example 3 after being stored for two months;

[0037] Figure 4 , the fluidity picture of the high solid content nano-alumina dispersion of Example 4 after being stored for two months;

[0038] Figure 5 , the fluidity picture of the high solid content nano-alumina dispersion of Comparative Example 1 after being stored for two months;

[0039] Figure 6 , The fluidity picture of the high solid content nano-alumina dispersion of Comparative Example 2 after being stored for two months. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The experimental methods for which specific conditions are not specified in the examples are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be purchased commercially.

[0041] Example 1

[0042] The first aspect of the present embodiment provides a method for preparing a high solid content nano-alumina dispersion, which comprises at least the following steps:

[0043] S1. Synthesizing nano-alumina powder by high temperature gas phase hydrolysis method;

[0044] S2. Dissolve the prepared nano-alumina powder in deionized water to obtain.

[0045] The high-temperature gas phase hydrolysis method is to react gasified elemental aluminum with chlorine to form gaseous aluminum trichloride, and the gaseous aluminum trichloride reacts with water vapor to form nano-alumina powder.

[0046] The temperature at which the gaseous aluminum chloride reacts with water vapor is 600°C.

[0047] The median particle size D50 of the nano-alumina powder is 0.108 μm.

[0048] The water content of the nano-alumina powder is 3.89%.

[0049] The pH value of the nano-alumina powder is 4.01.

[0050] The zeta potential of the nano-alumina powder is 6.1 mV.

[0051] The repose angle of the nano-alumina powder is 42°.

[0052] The bulk density of the nano-alumina powder is 0.0549 g / mL.

[0053] The median particle size D50 of nano-alumina powder was obtained by wet testing with a laser particle size analyzer, the moisture content was obtained by a Leichter moisture meter, the pH value and zeta potential were obtained by pH meter and zeta potential meter respectively, and the angle of repose and bulk density were obtained by a powder comprehensive tester.

[0054] The second aspect of this embodiment provides a solid content nano-alumina dispersion product prepared by the above preparation method.

[0055] The solid content of the nano-alumina powder in the product is 10wt%, that is, one part of nano-alumina powder and nine parts of deionized water.

[0056] Figure 1 This is a picture of the fluidity of the high solid content nano-alumina dispersion of Example 1 after being stored for two months.

[0057] Example 2

[0058] The first aspect of the present embodiment provides a method for preparing a high solid content nano-alumina dispersion, which comprises at least the following steps:

[0059] S1. Synthesizing nano-alumina powder by high temperature gas phase hydrolysis method;

[0060] S2. Dissolve the prepared nano-alumina powder in deionized water to obtain.

[0061] The high-temperature gas phase hydrolysis method is to react gasified elemental aluminum with chlorine to form gaseous aluminum trichloride, and the gaseous aluminum trichloride reacts with water vapor to form nano-alumina powder.

[0062] The temperature at which the gaseous aluminum chloride reacts with water vapor is 800°C.

[0063] The median particle size D50 of the nano-alumina powder is 0.118 μm.

[0064] The water content of the nano-alumina powder is 3.55%.

[0065] The pH value of the nano-alumina powder is 4.24.

[0066] The zeta potential of the nano-alumina powder is 7.7 mV.

[0067] The angle of repose of the nano-alumina powder is 39°.

[0068] The bulk density of the nano-alumina powder is 0.0307 g / mL.

[0069] The median particle size D50 of nano-alumina powder was obtained by wet testing with a laser particle size analyzer, the moisture content was obtained by a Leichter moisture meter, the pH value and zeta potential were obtained by pH meter and zeta potential meter respectively, and the angle of repose and bulk density were obtained by a powder comprehensive tester.

[0070] The second aspect of this embodiment provides a solid content nano-alumina dispersion product prepared by the above preparation method.

[0071] The solid content of the nano-alumina powder in the product is 20wt%, that is, two parts of nano-alumina powder and eight parts of deionized water.

[0072] Figure 2 This is a picture of the fluidity of the high solid content nano-alumina dispersion of Example 2 after being stored for two months.

[0073] Example 3

[0074] The first aspect of the present embodiment provides a method for preparing a high solid content nano-alumina dispersion, which comprises at least the following steps:

[0075] S1. Synthesizing nano-alumina powder by high temperature gas phase hydrolysis method;

[0076] S2. Dissolve the prepared nano-alumina powder in deionized water to obtain.

[0077] The high-temperature gas phase hydrolysis method is to react gasified elemental aluminum with chlorine to form gaseous aluminum trichloride, and the gaseous aluminum trichloride reacts with water vapor to form nano-alumina powder.

[0078] The temperature at which the gaseous aluminum chloride reacts with water vapor is 600°C.

[0079] The median particle size D50 of the nano-alumina powder is 0.104 μm.

[0080] The water content of the nano-alumina powder is 4.17%.

[0081] The pH value of the nano-alumina powder is 4.07.

[0082] The zeta potential of the nano-alumina powder is 7.3 mV.

[0083] The repose angle of the nano-alumina powder is 41°.

[0084] The bulk density of the nano-alumina powder is 0.0479 g / mL.

[0085] The median particle size D50 of nano-alumina powder was obtained by wet testing with a laser particle size analyzer, the moisture content was obtained by a Leichter moisture meter, the pH value and zeta potential were obtained by pH meter and zeta potential meter respectively, and the angle of repose and bulk density were obtained by a powder comprehensive tester.

[0086] The second aspect of this embodiment provides a solid content nano-alumina dispersion product prepared by the above preparation method.

[0087] The solid content of the nano-alumina powder in the product is 20wt%, that is, two parts of nano-alumina powder and eight parts of deionized water.

[0088] Figure 3 This is a picture of the fluidity of the high solid content nano-alumina dispersion of Example 3 after being stored for two months.

[0089] Example 4

[0090] The first aspect of the present embodiment provides a method for preparing a high solid content nano-alumina dispersion, which comprises at least the following steps:

[0091] S1. Synthesizing nano-alumina powder by high temperature gas phase hydrolysis method;

[0092] S2. Dissolve the prepared nano-alumina powder in deionized water to obtain.

[0093] The high-temperature gas phase hydrolysis method is to react gasified elemental aluminum with chlorine to form gaseous aluminum trichloride, and the gaseous aluminum trichloride reacts with water vapor to form nano-alumina powder.

[0094] The temperature at which the gaseous aluminum chloride reacts with water vapor is 500°C.

[0095] The median particle size D50 of the nano-alumina powder is 0.118 μm.

[0096] The water content of the nano-alumina powder is 3.34%.

[0097] The pH value of the nano-alumina powder is 4.14.

[0098] The zeta potential of the nano-alumina powder is 8.5 mV.

[0099] The repose angle of the nano-alumina powder is 36°.

[0100] The bulk density of the nano-alumina powder is 0.0369 g / mL.

[0101] The median particle size D50 of nano-alumina powder was obtained by wet testing with a laser particle size analyzer, the moisture content was obtained by a Leichter moisture meter, the pH value and zeta potential were obtained by pH meter and zeta potential meter respectively, and the angle of repose and bulk density were obtained by a powder comprehensive tester.

[0102] The second aspect of this embodiment provides a solid content nano-alumina dispersion product prepared by the above preparation method.

[0103] The solid content of the nano-alumina powder in the product is 30wt%, that is, three parts of nano-alumina powder and seven parts of deionized water.

[0104] Figure 4 This is a picture of the fluidity of the high solid content nano-alumina dispersion of Example 4 after being stored for two months.

[0105] Comparative Example 1

[0106] The specific implementation of this comparative example is basically the same as that of Example 1, except that this comparative example adopts commercially available nano-alumina powder to be dissolved in deionized water to prepare a nano-alumina dispersion with a high solid content.

[0107] The median particle size D50 of the nano-alumina powder is 0.094 μm.

[0108] The water content of the nano-alumina powder is 3.15%.

[0109] The pH value of the nano-alumina powder is 5.13.

[0110] The zeta potential of the nano-alumina powder is 9.5 mV.

[0111] The repose angle of the nano-alumina powder is 40°.

[0112] The bulk density of the nano-alumina powder is 0.0344 g / mL.

[0113] The median particle size D50 of nano-alumina powder was obtained by wet testing with a laser particle size analyzer, the moisture content was obtained by a Leichter moisture meter, the pH value and zeta potential were obtained by pH meter and zeta potential meter respectively, and the angle of repose and bulk density were obtained by a powder comprehensive tester.

[0114] The solid content of the nano-alumina powder in the high-solid-content nano-alumina dispersion is 20wt%, that is, two parts of nano-alumina powder and eight parts of deionized water.

[0115] Figure 5 This is a picture of the fluidity of the high solid content nano-alumina dispersion of Comparative Example 1 after being stored for two months.

[0116] Comparative Example 2

[0117] The specific implementation of this comparative example is basically the same as that of Example 1, except that this comparative example adopts commercially available nano-alumina powder to be dissolved in deionized water to prepare a nano-alumina dispersion with a high solid content.

[0118] The median particle size D50 of the nano-alumina is 0.105 μm.

[0119] The water content of the nano-alumina powder is 4.32%.

[0120] The pH value of the nano-alumina powder is 3.95.

[0121] The zeta potential of the nano-alumina powder is 7.8 mV.

[0122] The repose angle of the nano-alumina powder is 46°.

[0123] The bulk density of the nano-alumina powder is 0.042 g / mL.

[0124] The median particle size D50 of nano-alumina powder was obtained by wet testing with a laser particle size analyzer, the moisture content was obtained by a Leichter moisture meter, the pH value and zeta potential were obtained by pH meter and zeta potential meter respectively, and the angle of repose and bulk density were obtained by a powder comprehensive tester.

[0125] The solid content of the nano-alumina powder in the high-solid-content nano-alumina dispersion is 20wt%, that is, two parts of nano-alumina powder and eight parts of deionized water.

[0126] Figure 6 This is a picture of the fluidity of the high-solid content nano-alumina dispersion of Comparative Example 2 after being stored for two months.

[0127] Performance Testing Methods

[0128] 1. Fluidity test: The fluidity of the high solid content nano-alumina dispersions prepared in Examples 1-4 and Comparative Examples 1-2 was observed after storage for 0, 1, 7, 14, 35, and 63 days. The results are shown in Table 1.

[0129] Table 1

[0130]

[0131]

Claims

1. A method for preparing a high solid content nano-alumina dispersion, characterized in that: At least the following steps are included: S1. Synthesizing nano-alumina powder by high temperature gas phase hydrolysis method; S2, dissolving the prepared nano-alumina powder in deionized water to obtain; The high-temperature gas phase hydrolysis method is to react gasified elemental aluminum with chlorine to form gaseous aluminum trichloride, and the gaseous aluminum trichloride reacts with water vapor to form nano-alumina powder.

2. The method for preparing a high solid content nano-alumina dispersion according to claim 1, characterized in that: The temperature of the reaction between the gaseous aluminum chloride and water vapor is 500-800°C.

3. The method for preparing a high solid content nano-alumina dispersion according to any one of claims 1 to 2, characterized in that: The median particle size D50 of the nano-alumina powder is less than 1 μm.

4. The method for preparing a high solid content nano-alumina dispersion according to claim 1, characterized in that: The water content of the nano-alumina powder is less than 5%.

5. The method for preparing a high solid content nano-alumina dispersion according to claim 1, characterized in that: The pH value of the nano-alumina powder is 3.5-4.

5.

6. The method for preparing a high solid content nano-alumina dispersion according to claim 1, characterized in that: The zeta potential of the nano-alumina powder is 6-10mV.

7. The method for preparing a high solid content nano-alumina dispersion according to claim 1, characterized in that: The repose angle of the nano-alumina powder is 35-45°.

8. The method for preparing a high solid content nano-alumina dispersion according to claim 1, characterized in that: The bulk density of the nano-alumina powder is 0.03-0.06 g / mL.

9. A product prepared according to the method for preparing a high-solid content nano-alumina dispersion according to any one of claims 1 to 8.

10. The product obtained by the method for preparing a high solid content nano-alumina dispersion according to claim 9, characterized in that: The solid content of the nano-alumina powder in the product is 10-30wt%.

Citation Information

Patent Citations

  • Manufacture method and device of nanometer alumina powder

    CN102502745A

  • Continuous preparation process of high purity nanometer alumina

    CN1810646A